Insect-machine hybrid system development and insect behavior study toward micro-robot implementation in search and rescue mission - Le Duc Long (Nanyang Technological University, 2022)
In recent decades, robotics for Urban Search and Rescue (USAR) mission has received the attention from researchers around the world. However, very few artificial robots have been ready to participate in real mission due to the hindrances in size, locomotion control, obstacles handling, computational load and power consumption. Insect-machine hybrid system or cyborg insect, which consists of a live insect integrated with a miniaturized controller system, arises as an alternative solution. This study presents the advancement in insect-computer hybrid system implementation by nanomaterial application, biological surveillance as well as electrical and digital control approach. Previous research about insect-machine hybrid lacks action inhibition study and voluntary motion in insect remained unmanageable. In this research, the author demonstrated first-ever in vivo on-demand muscle inhibition in beetle using neurotransmitter γ-aminobutyric acid-encapsulated liposome. GABA remained inactive inside the lipid bilayer container even after the drug was injected inside the beetle body but was released when heat was applied to the region of interest and immobilized the targeted muscle. Successful local drug delivery also suggests further application such as endurance enhancement in cyborg insect. In addition, pre-flight eye warming up in beetle has been confirmed to be actively controlled by the insect in order to enhance its flight performance in escape behavior. The discovery will lead to further investigation to improve the insect performance in rescue mission by enhancing the sensory system. Last but not least, the author has surveyed and developed indoor localization system based on Inertia Measurement Unit combined with Radio Frequency-based positioning method. The system is suitable for tracking the position of the insect-machine system in action inside a concealed environment while remains small and low power consumption.